How Much Delay Has to Be Tolerated in a Mobile Social Network? - Yanqin Zhu; Haojun Zhang; Qijin Ji (International Journal of Distributed Sensor Networks)
Message delivery in a mobile social network (MSN) is difficult due to the fact that the topology of such network is sparse and unstable. Various routing schemes for MSNs were proposed to make the message delivery robust and efficient. However, little research has been conducted to explore how much delay has to be tolerated for the message delivery from the source to the destination. Since the social relationships among nodes are stable during a certain period of time, it is expected that the delay of message delivery in MSNs could be modeled with a probability model. In this paper, we take the first step to address this issue. We firstly extract three routing models from the existing routing schemes for MSNs and then develop the probability models of the message transmission delay for each abstract routing model. The simulation results show that the theoretical models match very well the simulation trace statistics.